2020
DOI: 10.3390/antibiotics9080469
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli Isolated from Mastitic Dairy Cattle in Ukraine

Abstract: Bovine mastitis is the predominant cause for antimicrobial use on dairy farms and is a major source of economic losses in the dairy industry. In this study, the antimicrobial susceptibility profiles of common mastitis-causing pathogens, Staphylococcus aureus (n = 62), Streptococcus agalactiae (n = 46), and Escherichia coli (n = 129), were determined for dairy cattle with mastitis across 142 Ukrainian farms. The results showed that there were more gentamicin resistant S. aureus isolates (16.95%) identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
5
1
2
Order By: Relevance
“…Moreover, a previous study conducted in the same geographic area reported that 23.8% of S. aureus isolates were MRSA [52]. However, MRSA prevalence in the present study is significantly higher than that of other countries such as Croatia [56] and Ukraine [57].…”
Section: Discussioncontrasting
confidence: 70%
“…Moreover, a previous study conducted in the same geographic area reported that 23.8% of S. aureus isolates were MRSA [52]. However, MRSA prevalence in the present study is significantly higher than that of other countries such as Croatia [56] and Ukraine [57].…”
Section: Discussioncontrasting
confidence: 70%
“…Specifically for Europe, 14 of 15 studies reported less than 8% of E. coli isolates resistant to 3GCs. The single exception was a study by Elias et al (2020) who found 43.3% of 102 mastitis isolates in Ukraine to be resistant to ceftiofur. The authors stated that 'this finding could potentially be explained by the unrestricted use of extended-spectrum cephalosporins in rural farming of Ukraine, and more specifically by the preferred use of these antimicrobials for treatment of bovine mastitis'.…”
Section: Results Of the Elr By Bacteriummentioning
confidence: 99%
“…Microorganisms on the skin surface, milking equipment, and the environment may provoke mastitis (3,4). The main mastitis-causing pathogens in cows are Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli (5).…”
Section: Introductionmentioning
confidence: 99%